Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's simplify the expression \(\left(x^3\right)^2\) step-by-step.
Given expression: \(\left(x^3\right)^2\)
We will use the exponentiation rule for this simplification, which states that \((a^m)^n = a^{m*n}\).
In our expression:
- \(a = x\)
- \(m = 3\)
- \(n = 2\)
Applying the rule:
[tex]\[ (a^m)^n = x^{3 \cdot 2} = x^6 \][/tex]
Thus, the expression \(\left(x^3\right)^2\) simplifies to \(x^6\).
The correct answer is \( \boxed{x^6} \).
Therefore, the correct choice is:
C. [tex]\(x^6\)[/tex]
Given expression: \(\left(x^3\right)^2\)
We will use the exponentiation rule for this simplification, which states that \((a^m)^n = a^{m*n}\).
In our expression:
- \(a = x\)
- \(m = 3\)
- \(n = 2\)
Applying the rule:
[tex]\[ (a^m)^n = x^{3 \cdot 2} = x^6 \][/tex]
Thus, the expression \(\left(x^3\right)^2\) simplifies to \(x^6\).
The correct answer is \( \boxed{x^6} \).
Therefore, the correct choice is:
C. [tex]\(x^6\)[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.